A Status Review of the Bioactive Activities of Tiger Milk Mushroom Lignosus rhinocerotis (Cooke) Ryvarden - Nallathamby, Neeranjini; Phan, Chia-Wei; Seow, Syntyche Ling-Sing; Baskaran, Asweni; Lakshmanan, Hariprasath; Abd Malek, Sri N.; Sabaratnam, Vikineswary (Frontiers in Pharmacology, 2018)
Edible and medicinal mushrooms are regularly used in natural medicines and home remedies since antiquity for ailments like fever, inflammation, and respiratory disorders. Lignosus rhinocerotis (Cooke) Ryvarden is a polypore found in Malaysia and other regions in South East Asia. It can be located on a spot where a tigress drips milk while feeding, hence the name “tiger’s milk mushroom”. The sclerotium of L. rhinocerotis is highly sought after by the native communities in Malaysia to stave off hunger, relieve cough and asthma, and provide stamina. The genomic features of L. rhinocerotis have been described. The pharmacological and toxicity effects, if any, of L. rhinocerotis sclerotium have been scientifically verified in recent years. In this review, the validated investigations including the cognitive function, neuroprotection, immune modulation, anti-asthmatic, anti-coagulation, anti-inflammatory, anti-microbial/ anti-viral, anti-obesity, anti-cancer/ anti-tumor, and antioxidant properties are highlighted. These findings suggest that L. rhinocerotis can be considered as an alternative and natural medicine in the management of non-communicable diseases. However, there is a paucity of validation studies including human clinical trials of the mycochemicals of L. rhinocerotis.